2017
DOI: 10.1016/j.apsb.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The current agonists and positive allosteric modulators of α 7 nAChR for CNS indications in clinical trials

Abstract: The alpha-7 nicotinic acetylcholine receptor (α7 nAChR), consisting of homomeric α7 subunits, is a ligand-gated Ca2+-permeable ion channel implicated in cognition and neuropsychiatric disorders. Enhancement of α7 nAChR function is considered to be a potential therapeutic strategy aiming at ameliorating cognitive deficits of neuropsychiatric disorders such as Alzheimer's disease (AD) and schizophrenia. Currently, a number of α7 nAChR modulators have been reported and several of them have advanced into clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 156 publications
(190 reference statements)
1
92
0
1
Order By: Relevance
“…Drugs displaying disease‐modifying properties are still not available for AD. Improving the function of the α7nAChR has gained increasing interest in this context with several drug candidates having been developed or currently under development to treat AD symptoms (Bertrand & Terry, ; Yang et al, ). Aβ, an important component of AD development, is known to impact on the function of the α7nAChR although the precise functional effect of Aβ on α7nAChRs is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs displaying disease‐modifying properties are still not available for AD. Improving the function of the α7nAChR has gained increasing interest in this context with several drug candidates having been developed or currently under development to treat AD symptoms (Bertrand & Terry, ; Yang et al, ). Aβ, an important component of AD development, is known to impact on the function of the α7nAChR although the precise functional effect of Aβ on α7nAChRs is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The α7nACh receptor is involved in learning and memory processes by inducing LTP, and its function is altered in the course of AD pathology (Bertrand, Lee, Flood, Marger, & Donnelly-Roberts, 2015;Gotti et al, 2006). Accordingly, restoring its activity has been proven beneficial in a variety of experimental models as well as in clinical trials (Ma et al, 2014;Thomsen, Hansen, Timmerman, & Mikkelsen, 2010;Yang, Xiao, Sun, & Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, when consulting some reviews that provide intense detail about the various modulators of α7 nAChR, we observed that the modulators that interact with these receptors by an allosteric mechanism are in smaller proportion relative to regular agonists. Interestingly, these compounds may interact with α7 nAChR either as positive or negative allosteric modulators (PAMs or NAMs).…”
Section: Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 98%
“…α7 nAChR is present on synaptic regions and is therefore directly related to neurotransmission. For instance, ACh, as its natural agonist, activates this receptor for signaling in the synapse . This receptor also plays a role in delivering glutamate to the cerebellum and hippocampus, and it also may be capable of interacting with Aβ peptide .…”
Section: Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%
See 1 more Smart Citation